2018
DOI: 10.3390/nu10091306
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Binge Eating: Psychometric Properties of the Eating Beliefs Questionnaire (EBQ-18) in Eating Disorder, Obese, and Community Samples

Abstract: Binge eating is a core diagnostic feature of bulimia nervosa, binge eating disorder, anorexia nervosa binge/purge type, and is a common feature of “other specified” and “unspecified” feeding and eating disorders. It has been suggested that specific metacognitive beliefs about food, eating, and binge eating may play a key role in the maintenance of binge eating behaviour. The Eating Beliefs Questionnaire (EBQ-18) provides a brief self-report assessment tool measuring three types of metacognitive beliefs: negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 34 publications
5
33
0
4
Order By: Relevance
“…These results are also consistent with the examination of the factor structure EBQ-18 with a nonclinical sample. [ 14 17 ] Further, these results are in line with the results of the previous study that found an earlier, two subscale version of the EBQ with nonclinical samples. [ 13 34 ] The normal Chi-square should be <3 for an acceptable model.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These results are also consistent with the examination of the factor structure EBQ-18 with a nonclinical sample. [ 14 17 ] Further, these results are in line with the results of the previous study that found an earlier, two subscale version of the EBQ with nonclinical samples. [ 13 34 ] The normal Chi-square should be <3 for an acceptable model.…”
Section: Discussionsupporting
confidence: 90%
“…To assess the construct validity of the EBQ-18 and determine the fit of the factor and subscales structure obtained by Burton et al ,[ 14 17 ] CFA was performed. Based on the results of Eating Beliefs scale, the three-factor model was tested [ Table 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies should also examine the differences in scores between clinical eating disorder groups and non-clinical controls, with binge eating status verified by a clinician interview, such as the EDE. Furthermore, it is important for future studies to examine the EBQ-18’s sensitivity to treatment and test-retest reliability (recent research has examined the utility of the EBQ-18 in both general and clinical eating disorder samples [ 44 ]).…”
Section: Discussionmentioning
confidence: 99%